A comprehensive review on 4D printing and applications of thermo-induced shape memory polymers - Jian Li; Zhihong Liang; Tengjie Li; Qiang Wan; Xicheng Huang; Qianhua Kan (International Journal of Smart and Nano Materials)
Thermo-induced Shape Memory Polymers (TSMPs) and their corresponding 4D printing technology are at the forefront of current research. In this work, we review the progress from TSMPs to 4D printing and their corresponding applications. Firstly, taking thermally activated TSMPs as an example, the shape memory behavior is explained, and various shape memory experiments and mechanisms, as well as constitutive models, are discussed. This comprehensive information is designed to provide a solid understanding of TSMPs. Moreover, the history of 4D printing and various technologies used in 4D printing are introduced, and potential printing methods are summarized. These insights can guide researchers in selecting appropriate techniques for practical applications. The applications of 4D printed TSMPs are then outlined, with a focus on metamaterials and various industry cases that provide a clear understanding of what 4D printing can achieve. This knowledge will open new doors for innovative applications. Finally, the current research status is summarized, and the existing research gaps and future development directions are pointed out. Through this review, we aim to offer a comprehensive understanding of the journey from TSMPs to 4D printing and their applications so as to support further research and the promotion of 4D printing of TSMPs in the field of smart materials.